Market or regulation? the competition effect between green finance and environmental enforcement on environmental quality and its “dominate-follow” pattern - Tang, Xinmeng; Qin, Tao; Kholaif, Moustafa Mohamed Nazief Haggag Kotb; Zhao, Xinyan (Springer, 2024)
Current research on environmental instruments often isolates the two mainstream types, market-based and regulation-based, overlooking their real-world interactions. In response, the intensity gap variable (EII_GAP) is constructed to link various instruments into a united system. Thus, based on the spatial econometrics of the spatial panel Durbin model (SPDM), the collective effects between market- and regulation-based environmental instruments on environmental quality are explored. Moreover, the political strategies for maximizing environmental benefits are discussed. Results show that the interaction pattern between market- and regulation-based environmental instruments on environmental quality is characterized by competition rather than cooperation. A unit widening in the intensity gap leads to 17 to 18% and 12 to 18% units of environmental quality improvement in local and adjacent areas, respectively. Furthermore, the “dominate-follow” approach as the most effective mode for maximizing environmental effects is proposed. This study recommends employing one type of instrument as the dominant while the other as the auxiliary. In provinces where one kind of environmental instrument takes domination, the environmental quality could be increased by around 8 to 113% after taking another contrary instrument as the auxiliary.